SPECIES COMPOSITION OF THE MAIN PESTS OF FIG AND THE ADVANTAGES OF A HARMONIZED SYSTEM OF CONTROL AGAINST THEM (Scientific journal of the Fergana State University, 2024)
The article provides information on the species composition of the main pests of figs and the benefits of a coordinated system of combating them.The climatic conditions of Uzbekistan are favorable for the cultivation of crops adapted to the subtropical climate. These include figs. These tree-shrubs have been planted since ancient times and have become a branch of horticulture for the countries of Central Asia, including the people of Uzbekistan.It is important that the work and expenses spent on protecting agricultural crops from pests and diseases pay off. Especially in the period of the current market economy, it is necessary not to allow the cost of the grown products to be high. In the first and second harvest of figs, the additional income obtained due to the chemical control against the fig moth is recorded.